The influence of leadership, job satisfaction and work discipline on employee performance (Perum Perhutani Bandung City Forest Management Unit) - Fitrianty, Ervani; Siddiq, Andika Mochamad (Institute of Computer Science (IOCS), 2024)
The study was carried out in a State-Owned Enterprise that was in charge of planning, managing, cultivating, and protecting forests. Employee performance in the Perhutani Forest Management Unit (KPH) in Bandung City fell short of expectations, pointing to a downturn. This is demonstrated by poor work discipline monitoring, subpar job satisfaction, and applied leadership. In the Forest Management Unit (KPH) of Perhutani in Bandung City, efficient management and assessment are essential. The accomplishment of organizational objectives and the execution of work plans depend on these procedures. The study aims to ascertain how work discipline, leadership, and job happiness affect employees' performance at the Perhutani Forest Management Unit (KPH) in Bandung City. This study employs a quantitative methodology that is focused on verification and description. Fifty respondents made up the sample that was used in this research. Leadership positively impacts employee performance, is slightly influenced by work discipline, and partially contributes to job happiness. In general, work discipline, leadership, and job happiness significantly influence how well employees perform.